2014
DOI: 10.1111/jgs.12711
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Public Reporting on Physical Restraints and Antipsychotic Use in Nursing Home Residents with Severe Cognitive Impairment

Abstract: This analysis suggests that public reporting of physical restraint use had the unintended consequence of increasing use of antipsychotics in NH residents with severe cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
2
44
0
1
Order By: Relevance
“…Studies have also shown that providers, 12 nursing homes in particular, 2951,52 improve in response to publicly published performance measures. Furthermore, improvement is stronger in more competitive markets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that providers, 12 nursing homes in particular, 2951,52 improve in response to publicly published performance measures. Furthermore, improvement is stronger in more competitive markets.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of residents physically restrained is a quality indicator that may be inversely related to an NH's use of antipsychotics and other chemical restraints . Medicare is another federal insurance program specifically for older adults and individuals with disabilities, but Medicare reimburses at a higher rate than Medicaid.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Th e HRRP is federal policy targeted specifi cally to the Medicare population, and we believe that the choice of states captures the heterogeneity of benefi ciaries. 31 Th e rate of unplanned readmissions decreased 0.3% from 2009 to 2011, leading us to believe that there has been no major trend change in COPD readmissions more recently. Additionally, the study population aft er exclusion of patients who died during the index hospitalization may not refl ect the entire COPD Medicare population.…”
Section: Similar To Work In Other Conditions By Jencks Et Al 12 Andmentioning
confidence: 99%